Screening of two Trichogramma species, native to southeastern Brazil, for the control of tobacco budworm - SANTOS-ANDRADE, GILBERTO; PRATISSOLI, DIRCEU; BARROS, REGINALDO; BOLSONI-ZAGO, HUGO; DE AZEVEDO PEREIRA, ALEXANDRE IGOR; PIN DALVI, LEANDRO (Revista Colombiana de Entomología, 2010)
The biological control of insect pests using parasitoids may have limited success without an understanding of the effect of temperature on natural enemies. The objective was to determine the parasitism, egg viability and sex ratio of Trichogramma exiguum and Trichogramma acacioi (Hymenoptera: Trichogrammatidae) to control Heliothis virescens (Lepidoptera: Noctuidae) eggs after two generations on eggs of Anagasta kuehniella at 18, 20, 25, 30 and 33ºC. The increase in temperature favored the parasitism of T. exiguum. The egg viability of T. exiguum ranged between 70.1 and 97.1% and from 81.5 to 98.4% for T. acacioi in H. virescens eggs. The sex ratio of T. acacioi was constant at all temperatures studied, with only females in the progeny. Trichogramma exiguum reared in H. virescens eggs met the standards of quality control for mass production. Trichogramma exiguum showed higher parasitism than T. acacioi at high temperatures. However, both species had low parasitism on H. virescens eggs.